Primary thyroid angiosarcoma: A systematic review. (July 2018) - De Felice, F.; Moscatelli, E.; Orelli, S.; Bulzonetti, N.; Musio, D.; Tombolini, V.
Highlights: Thyroid angiosarcoma (TAS) is a rare entity and its management is still debated. This is the largest updated analysis of literature data in TAS patients. This analysis suggests that early diagnosis and multidisciplinary approach could influence outcome. Abstract: Thyroid angiosarcoma (TAS) is rare and represents a very aggressive malignancy. Its rarity is principally linked to two major pitfalls. Firstly, TAS histopathology diagnosis can be difficult; second, the limited clinical experience with this condition can make its management complex. We conducted a detailed systematic review, focusing on the knowledge available regarding TAS etiopathogenesis, treatment options and prognosis. The aim is to present the main TAS characteristics and to summarize the clinical experiences described worldwide, in order to provide a useful clinical tool.